The Role of Product Innovation on an Improvement of the Organization’s Reputation /A Field Study in State Organization for Marketing of Oil (SOMO) - Jawad, Aya Shaheen; Al-Rabia’i, Saadoun Hammoud Jatheer (Journal of Economics and Administrative Sciences, 2021)
This paper aims to verify the existence of relationships between product innovation and the reputation of the organization. The study problem is that the State Organization for Marketing of Oil (SOMO) system is inflexible in terms of marketing procedures and needs innovative, unconventional methods in innovating its products and improving performance. The reputation of the organization. The importance of the study lies in that it is an attempt to raise the interest of SOMO in its approach to the research variables in order to enhance its competitive position in the future and improve the marketing business environment, which contributes to enhancing the reputation of the organization by product innovation. The study sample included 221 of SOMO employees and employees. Data and information were collected using questionnaires and personal interviews. As well as, the field presence of the researchers. The data were analyzed using the statistical program (SPSS v.24). The most prominent findings of the study showed that any change in product innovation can contribute to bringing about a change in the reputation of the organization